2005
DOI: 10.1158/1078-0432.ccr-1004-0013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Therapeutic Index: From Nonmyeloablative and Myeloablative toward Pretargeted Radioimmunotherapy for Metastatic Prostate Cancer

Abstract: Purpose: New strategies that target selected molecular characteristics and result in an effective therapeutic index are needed for metastatic, hormone-refractory prostate cancer. Experimental Design: A series of preclinical and clinical studies were designed to increase the therapeutic index of targeted radiation therapy for prostate cancer. 111In/ 90 Y-monoclonal antibody (mAb), m170, which targets aberrant sugars on abnormal MUC1, was evaluated in androgenindependent prostate cancer patients to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…For antibody therapies utilizing radiometal and toxin conjugates, slow systemic clearance may cause dose limiting toxicities to the bone marrow and other healthy tissue [119,120]. Similarly, slow clearance may reduce the sensitivity of imaging or necessitate long waiting periods due to high background signals in the blood and other well perfused tissues [29].…”
Section: Systemic Clearance and Antibody Sizementioning
confidence: 99%
“…For antibody therapies utilizing radiometal and toxin conjugates, slow systemic clearance may cause dose limiting toxicities to the bone marrow and other healthy tissue [119,120]. Similarly, slow clearance may reduce the sensitivity of imaging or necessitate long waiting periods due to high background signals in the blood and other well perfused tissues [29].…”
Section: Systemic Clearance and Antibody Sizementioning
confidence: 99%
“…Using MAbs DF3 and B27.29, Zellweger et al have shown that expression of human MUC1 (urinary mucin 1) slowly but gradually increased from BPH to prostatic intraepithelial neoplasia (PIN) and through the various stages of CaP [134]. DeNardo et al have tested MUC1 expression on CaP TMAs using three anti-MUC1 MAbs (BrE3, B27.29, and HMFG1), and found that the profile of BrE3 showed a strong correlation between CaP stage and increase in MUC1 staining (P<0.001) [135].…”
Section: The Expression Of Muc1 On Human Capmentioning
confidence: 99%
“…In another trial study, the 90 Y-m170 was further evaluated in androgen-independent CaP patients to determine MTD and efficacy of nonmyeloablative radioimmunotherapy (RIT) and myeloablative combined modality RIT with paclitaxel [135]. To enhance the tumor to liver therapeutic index, a cathepsin degradable MAb linkage ( 90 Y-DOTA-peptide-m170) was used in the combination therapy protocol.…”
Section: Muc1-specific Mabs With Targeting Radionuclides Therapymentioning
confidence: 99%
“…121 The projected assembly of covalent tri-and tetravalent PEG-scFv complexes for pretargeted RIT in metastatic prostate cancer has also been described. 122 The MUC1-driven expression of the sodium iodide symporter in breast tumor xenografts led to increased radioactivity uptake by tumor cells. 123 A divalent scFv-angiotensin II fusion protein demonstrated improved tumor distribution in tumorbearing mice.…”
Section: Preclinical Developmentmentioning
confidence: 99%